2015
DOI: 10.1152/japplphysiol.00030.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on long-term facilitation and chemosensitivity during NREM sleep

Abstract: The reason for increased sleep-disordered breathing with a predominance of central apneas in the elderly is unknown. We speculate that ventilatory control instability may provide a link between aging and the onset of unstable breathing during sleep. We sought to investigate potential underlying mechanisms in healthy, elderly adults during sleep. We hypothesized that there is 1) a decline in respiratory plasticity or long-term facilitation (LTF) of ventilation and/or 2) increased ventilatory chemosensitivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
2
18
1
Order By: Relevance
“…Instead, we noted increased hypocapnic chemoreflex sensitivity during sleep in elderly adults relative to the younger group, indicative of increased central chemoreceptor activity. These findings corroborate our previous findings demonstrating increased peripheral chemoreceptor activity in older adults (16).…”
Section: Mechanism(s) Of the Age Effectsupporting
confidence: 93%
See 3 more Smart Citations
“…Instead, we noted increased hypocapnic chemoreflex sensitivity during sleep in elderly adults relative to the younger group, indicative of increased central chemoreceptor activity. These findings corroborate our previous findings demonstrating increased peripheral chemoreceptor activity in older adults (16).…”
Section: Mechanism(s) Of the Age Effectsupporting
confidence: 93%
“…In a separate study, steady-state loop gain was also lower in older vs. younger OSA patients (22). Conversely, we have demonstrated that the elderly have higher peripheral chemoresponsiveness than young adults (16), which may contribute to increased periodic breathing. Given the conflicting findings, it is important to clarify the underlying pathophysiology for SDB in the elderly, which may inform targeted therapies of sleep apnea in the elderly.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Chowdhuri and colleagues demonstrated in humans that aging is linked to a reduction in the magnitude of long-term facilitation during non-rapid eye movement sleep since long-term facilitation was found in young but not older men ( Chowdhuri et al, 2015 ; Chowdhuri et al, 2010 ). The authors suggested that the absence of ventilatory long-term facilitation in older adults during sleep could be due to an age-dependent decline in raphe neuronal activity, reduced availability of serotonin, or an age-related decrease in serum testosterone levels in older men ( Chowdhuri et al, 2015 ; Chowdhuri et al, 2010 ). However, their study was not designed to tease out the relative contribution of age vs. reduction in sex hormone levels on the magnitude of ventilatory long-term facilitation.…”
Section: Factors That Impact the Magnitude Of Respiratory Plasticitymentioning
confidence: 99%